2013
DOI: 10.1111/head.12212
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16 rs2651899 Variant Is a Risk Factor for Chinese Common Migraine Patients

Abstract: Our data suggested that rs2651899 variant in PRDM16 plays a potential role in Chinese MO migraine susceptibility, and gender may not play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
5
24
1
Order By: Relevance
“…Previously, we examined the variations among PRDM16 , LRP1 and TRPM8 in a small sample of Chinese migraine patients and found that PRDM16 was associated with MO susceptibility . This result was different from Freilinger's report, which may have been due to our small‐scale sample .…”
contrasting
confidence: 72%
“…Previously, we examined the variations among PRDM16 , LRP1 and TRPM8 in a small sample of Chinese migraine patients and found that PRDM16 was associated with MO susceptibility . This result was different from Freilinger's report, which may have been due to our small‐scale sample .…”
contrasting
confidence: 72%
“…Rs2651899 has also been confirmed to be a risk factor for migraine in a meta-analysis including both clinical- and population-based cohorts [21] and in MO patients in a Chinese cohort [29]. The minor allele of this SNP was associated with an increased risk of migraine also in our Swedish cohort.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, Chasman et al described association between SNPs in the PRMD16 , TRPM8 , and LRP1 genes. Recent studies identified association between an SNP in the SLC39A12 gene and the risk for migraine or MWoA in different populations, but failed to find association with SNPs in the GALNT16 gene . In addition, interethnic variability in the associations exists, as LRP1 was found to be associated with the risk for migraine in Indians, but not in Chinese or Swedish individuals …”
Section: Clinical Epidemiological Biochemical Experimental and Phmentioning
confidence: 99%